Critical pollutant emissions from the Indian telecom network. (February 2015) - Sahu, S.K.; Schultz, M.G.; Beig, G.
Abstract: In recent years, India developed the world's 2nd largest telecom network based largely on mobile phone connections. The energy demand of the telecom sector especially in rural areas is mainly fueled by diesel combustion in mid-size generators due to either lack of grid power or unstable provision of electricity. This study quantifies the magnitude of emissions from the Indian telecom sector and presents a gridded inventory for the year 2011 with a spatial distribution derived on the provincial level including information on urban versus rural telecom installations. The estimated total NO x, PM, CO, BC, SO2, HC and CO2 emissions are found to be 295 ± 196 Gg/yr, 155 ± 108 Gg/yr, 61 ± 41 Gg/yr, 28 ± 18 Gg/yr, 114 ± 12 Gg/yr 19.50 ± 13 Gg/yr and 27.9 ± 12 million tons/yr, respectively. The future development of emissions from this sector will depend on the rate of electrification and possible market saturation. Air quality in rural areas of India could be improved by replacing diesel generators with renewable energy sources or electricity from the grid. Highlights: Telecom is rapidly spreading across the world with social economic development. The energy demand from telecom is big challenge especially in developing India. Diesel is only alternative especially in rural drive to emission of huge pollutant. First ever estimation for anthropogenic emission from world's 2nd largest telecom. We discussed and recommend possible mitigation strategy to control telecom related pollution by 2020.